Ultrasound shear wave elastography for assessing diaphragm function in mechanically ventilated patients: a breath-by-breath analysis - Fossé, Quentin; Poulard, Thomas; Niérat, Marie-Cécile; Virolle, Sara; Morawiec, Elise; Hogrel, Jean-Yves; Similowski, Thomas; Demoule, Alexandre; Gennisson, Jean-Luc; Bachasson, Damien; Dres, Martin (Critical care (London, England), 2020)
Background Diaphragm dysfunction is highly prevalent in mechanically ventilated patients. Recent work showed that changes in diaphragm shear modulus (ΔSMdi) assessed using ultrasound shear wave elastography (SWE) are strongly related to changes in Pdi (ΔPdi) in healthy subjects. The aims of this study were to investigate the relationship between ΔSMdi and ΔPdi in mechanically ventilated patients, and whether ΔSMdi is responsive to change in respiratory load when varying the ventilator settings. Methods A prospective, monocentric study was conducted in a 15-bed ICU. Patients were included if they met the readiness-to-wean criteria. Pdi was continuously monitored using a double-balloon feeding catheter orally introduced. The zone of apposition of the right hemidiaphragm was imaged using a linear transducer (SL10-2, Aixplorer, Supersonic Imagine, France). Ultrasound recordings were performed under various pressure support settings and during a spontaneous breathing trial (SBT). A breath-by-breath analysis was performed, allowing the direct comparison between ΔPdi and ΔSMdi. Pearson’s correlation coefficients ( r ) were used to investigate within-individual relationships between variables, and repeated measure correlations ( R ) were used for determining overall relationships between variables. Linear mixed models were used to compare breathing indices across the conditions of ventilation. Results Thirty patients were included and 930 respiratory cycles were analyzed. Twenty-five were considered for the analysis. A significant correlation was found between ΔPdi and ΔSMdi ( R = 0.45, 95% CIs [0.35 0.54], p < 0.001). Individual correlation displays a significant correlation in 8 patients out of 25 ( r = 0.55–0.86, all p < 0.05, versus r = − 0.43–0.52, all p > 0.06). Changing the condition of ventilation similarly affected ΔPdi and ΔSMdi. Patients in which ΔPdi–ΔSMdi correlation was non-significant had a faster respiratory rate as compared to that of patient with a significant ΔPdi–ΔSMdi relationship (median (Q1–Q3), 25 (18–33) vs. 21 (15–26) breaths.min −1 , respectively). Conclusions We demonstrate that ultrasound SWE may be a promising surrogate to Pdi in mechanically ventilated patients. Respiratory rate appears to negatively impact SMdi measurement. Technological developments are needed to generalize this method in tachypneic patients. Trial registration NCT03832231 .